2021
DOI: 10.1016/j.ijscr.2021.106480
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of shoulder manipulation under ultrasound-guided cervical nerve root block for frozen shoulder for patient with diabetes mellitus: A retrospective cohort study

Abstract: Introduction Shoulder manipulation under ultrasound-guided cervical nerve root block (MUC) gives good clinical results in patients with frozen shoulder 1 week after the procedure. However, some patients are refractory to MUC. The present study was performed to investigate the prognostic factors of MUC for frozen shoulder. Methods We evaluated 73 frozen shoulders (70 patients) to investigate the prognostic factors of MUC. The patients' mean age was 56.6 years, and 60% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…We have used silent manipulation in the hope of removing these burdens. Several previous studies have reported on the safety of conduction anesthesia and the effectiveness of manipulation [ 8 , 9 , 11 ]. A magnetic resonance imaging study in 30 patients who underwent manipulation under an ultrasound-guided cervical nerve root block found a significant improvement in pain with no fractures [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have used silent manipulation in the hope of removing these burdens. Several previous studies have reported on the safety of conduction anesthesia and the effectiveness of manipulation [ 8 , 9 , 11 ]. A magnetic resonance imaging study in 30 patients who underwent manipulation under an ultrasound-guided cervical nerve root block found a significant improvement in pain with no fractures [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have been experimenting with ultrasoundguided treatment for frozen shoulder since about 2010 [5,6]. This treatment, subsequently named "silent manipulation" by Minagawa [7], involves manipulation of the shoulder joint under local anesthetic nerve block and has been widely used [8][9][10]. There have been no serious complications arising from ultrasound-guided cervical nerve root block in previous studies [8][9][10], and its safety has been validated [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the most commonly observed orthopedic conditions, with a prevalence of 2-5% in the general population, with a risk increase to 10-40% among patients with diabetes mellitus (DM) (2,3). Moreover, some authors have reported poorer outcomes in patients with diabetic frozen shoulder (4)(5)(6)(7). This condition commonly occurs in patients aged 40-60 years, with incidence peaking in the mid-50s (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients are refractory to MUC, and few studies have focused on the prognostic factors of MUC (5,23). Therefore, this study was conducted to investigate the prognostic factors of MUC for frozen shoulder.…”
Section: Introductionmentioning
confidence: 99%